PENGEKALAN DAN PERALIHAN BAHASA DALAM KALANGAN GENERASI MUDA ETNIK KEDAYAN DI BEKENU SARAWAK = [LANGUAGE MAINTENANCE AND SHIFT AMONG THE ETHNIC YOUTH OF KEDAYANS IN BEKENU, SARAWAK] - Dilah, Tuah; Remmy, Gedat; Muhammad Jazlan, Ahmad Khiri; Chong, Shin (Index Copernicus International, 2020)
The ubiquity of various minority languages in Sarawak has formed a phenomenon of language shift and maintenance at an individual and societal level. This scenario was caused by social conditions as well as the clash between the more dominant majority language. In the context of Sarawak, there are some majority languages which are dominant such as the Sarawak Malay dialect, Iban, Malay and the English language. The status, position and influence of these languages have influenced the society’s language choice in Sarawak. The Kedayan language is one of the minority language that is present in Bekenu, Sarawak exposed to the clash with the majority’s languages. The findings based on observation of the vocabulary knowledge found there is a lack of examinations done of the Kedayan ethnic minorities from the sociolinguistic standpoint. This study was carried out through a sociolinguistic approach specifically Fishman (1972) domain analysis in a field study. A total of 30 respondents of Kedayan ethnic youths were selected in random for this study. The collected data were used to analyse and elaborate the language maintenance and shift phenomenon that occurred among the Kedayan’s ethnic youth in Bekenu, Sarawak. The findings of this study has found that the language maintenance and shift phenomenon of the Kedayan’s ethnic youth in Bekenu, Sarawak had occurred in a few specific domains only. From the standpoint of vitality and the ubiquitous language, the Kedayan language is in a safe status as it is still spoken by all generations.